El viaje en la novela latina: El Satiricón de Petronio y El asno de oro de Apuleyo - López Fonseca, Antonio (Revista de Filología Románica, 2006)
The aim of this paper is to show how in the latin novels is possible to find some basic formal and structural aspects of travel literature.